MAMMOGRAPHIC DENSITY AS A BREAST CANCER RISK FACTOR - N. A. Zakharova (Креативная хирургия и онкология)
The main aim of  this paper  is give the  detailed review on mammographic density  as a breast cancer  risk factor, classification and  methods of the  evaluation. Mammographic density  is one  of  the  well-known risk factor for  breast cancer.  Several studies  have  confirmed  that  women with high breast density  have a four-fold to six-fold  greater risk for developing breast cancer  than  women with  low breast density.  The association between breast density and other  breast cancer risk factors has been shown  in the number of studies. Thus, the reducing high mammographic density may become a new way for the primary prevention of the breast cancer.